Impact of farmer group participation on the adoption of sustainable farming practices—spatial analysis of New Zealand dairy farmers - Yang W; Wang L (John Wiley and Sons Ltd on behalf of Edgard Milhaud Foundation, 2023)
This paper analyzes the impact of participation in farmer groups on dairy farmers’ adoption of sustainable farming practices in New Zealand. A spatial propensity score matching method is used to consider the spatial dependence and social connections between farmers in the decision-making of farmer group participation and adoption of sustainable farming practices. The results show that farmers’ decisions of farmer group participation are affected by their neighbors’ choices, and participation in farmer groups has a positive effect on farmers’ adoption of sustainable farming practices. The findings indicate the important role of social interactions in farmers’ voluntary uptake of sustainable agricultural practices. Overall, the positive effect of farmer group participation on the adoption of sustainable agricultural practices highlights learning and knowledge spillover among farmers, which emerges as important to the formulation of sustainable farming policy.
Keywords: farmer group participation; spatial propensity score matching; sustainable agricultural practices